Effect of organic and inorganic amendments on amelioration of sodic soil and sustaining rice (Oryza sativa)-wheat (Triticum aestivum) productivity - SINGH, YASH PAL; ARORA, SANJAY; MISHRA, VINAY K; DIXIT, HIMANSHU; GUPTA, RAVINDRA K (The Indian Journal of Agricultural Sciences, 2018)
Management of degradation of sodic lands in arid and semi-arid regions is a global concern. Amelioration of these soils through chemical amendments like gypsum or phosphogypsum is a costly affair for resource poor farmers having sodic lands. Combined use of municipal solid waste (MSW) compost with chemical amendments can providea realistic solution for ameliorating sodic soils and sustaining crop productivity. A field experiment was conducted during 2015 to 2016 at Shivri, Lucknow on highly sodic soil [pH 9.8, exchangeable sodium percentage (ESP) 78, organic carbon (OC) 1.30 g/kg and gypsum requirement (GR) 15.2 t/ha] to evaluate the influence of organic and inorganic amendments on amelioration of sodic soils and sustaining productivity of rice (Oryza sativa L.)-wheat(Triticum aestivum L.) cropping system. The treatments consisted of T1: Gypsum (G) @ 50%GR, T2: Phosphogypsum (PG) @ 50%GR, T3: G @25%GR + on-farm MSW compost @10 t/ha, T4: PG @25%GR+ on-farm MSW compost @10 t/ha, T5: G @12.5%GR + on-farm MSW compost @10 t/ha + pressmud (PM) @10 t/ha, T6: PG @12.5%GR+ on-farm MSW compost @ 10 t/ha + PM @ 10 t/ha, T7: G @ 25%GR + industrial processed (IP) MSW compost @10 t/ha and T8: PG @ 25%GR + IP MSW compost @10 t/ha. The results indicated that, application of reduced dose (25% of GR) of gypsum (T3) in combination with on-farm MSW compost @10 t/ha reduced about 14% ESP and increased 11% soil bulk density, 54% infiltration rate, 10% soil organic carbon content, and 13% available N over the recommended practice (T1). Productivity of rice and wheat crops enhanced to the tune of 4 and 12 %, respectively and thus farmers can save about ` 29444.00/ha on account of reducing the quantity of gypsum or phosphogypsum without any significant yield loss and the saved amount can be utilized to bring more area under reclamation. The maximum N content in rice and wheat grain was recorded with treatment T4.